CATHODOLUMINESCENCE OF SYNTHETIC (DOPED WITH RARE-EARTH ELEMENTS) AND NATURAL ANHYDRITES - Baumer A.; Blanc Ph.; Cesbron F.; Ohnenstetter D. (My University, 1997)
In order to interpret cathodoluminescence (CL) spectra of natural anhydrites, synthetic crystals were indirectly obtained by precipitation of gypsum from solutions containing doping rare-earth elements (REE), and by transformation into anhydrite by dehydration at 800°C during 3 h. Analyses by ICP-MS of several anhydrites obtained from solutions containing 130 ppm of REE clearly showed that light REE (LREE) can be concentrated to up to 2000–3000 ppm in the solid; heavy REE (HREE) are less prone to enter the structure and only 255 ppm were found for Lu.REE such as Ce3+, Pr3+, Sm3+, Eu2+, Gd3+, Tb3+, Dy3+ and Tm3+ display strong CL emissions and spectra usually are complex except for three of them with intense emissions in the near UV domain: Ce3+ (306–327 nm), Gd3+ (314 nm) and Eu2+ (386 nm). In the near IR domain, only Nd3+ (874 nm) gives an important luminescence. Several natural anhydrites were examined for REE CL emissions: a sample from the Faraday uranium mine, Bancroft, Ontario, presents mainly a strong Ce3+ emission with traces of Eu2+, Dy3+, Sm3+ and Nd3+; in the anhydrite from Balazuc, France, Gd3+, Eu2+ and Dy3+ are the more abundant, followed by Ce3+ and traces of Tb3+ and Sm3+. A crystal, probably from Hall, Tyrol, displays Gd3+, Ce3+, Er3+, Tb3+, Dy3+ and Sm3+: its analysis by ICP-MS showed that the CL can be induced by only some ppm of these elements, even less than 1 ppm for Er3+ and Tb3+.